Labor Markets and the Crisis in Latin America and the Caribbean (A Preliminary Review for Selected Countries) - Freije-Rodríguez, Samuel; Murrugarra, Edmundo (World Bank, Washington, DC, 2012)
Countries in Latin America and the Caribbean are experiencing the impact of the international financial crisis on labor markets across different dimensions, such as employment, wages and the quality of labor market arrangements. This note reviews a selected group of countries to assess the speed and severity of labor market impacts. It identifies patterns in the changing labor market conditions, such as specific sectors or types of workers being affected. It also describes countries' preparedness and capacity to respond to the crisis and the specific policy responses being implemented. The review finds a large variation in impacts and responses in the context of increases in unemployment rates that range from 0.4 to 2.1 percentage points. The impacts of the crisis are evolving rapidly but seem to have a more noticeable negative effect among salaried workers in Brazil and Chile whereas in Colombia non-salaried workers have been affected the most. Mexico shows both types of workers as being seriously hit by the recession.